Hubungan Peran dan Sikap Perawat IGD dengan Pelaksanaan Triage Berdasarkan Prioritas - Ni Luh Dita Andrayoni; Made Martini; Nur Widya Putra; Kadek Yudi Aryawan (Journal of Telenursing (JOTING), 2019)
The purpose of this study was to study the relationship between the role and attitudes of emergency room nurses and the implementation of triage based on priorities. The research method used is descriptive correlational with cross sectional design. The results of the study showed the role of nurses with the implementation of triage of 25 people (65.8%), approved a positive attitude with the implementation of triage of 23 people (60.5%) and successfully carried out triage according to the SOP of 30 people (78.9%). The results of the study with the chi-square test p-value <0.05. In conclusion, there is a relationship between the role and attitudes of emergency nurses with the implementation of triage based on priorities. Keywords: Role, Attitude, Triage